Microneedle Sensors for Multiplex Applications: Toward Advanced Biomedical and Environmental Analysis (Adv. Sensor Res. 2/2023). Issue 2 (10th February 2023) - Omar, Rawan; Zheng, Youbin; Wang, Jing; Haick, Hossam
Abstract : Microneedle‐based Sensors In article number 2200032, Hossam Haick and co‐workers summarize the latest developments in microneedle‐based sensors and provide a comprehensive overview of the wide range of applications, ranging from materials and fabrication techniques to advanced sensor types in the biomedical and environmental fields, demonstrating the tremendous advantages of this emerging tool for clinical and sustainability‐related applications.